2019
DOI: 10.3389/fneur.2019.00374
|View full text |Cite
|
Sign up to set email alerts
|

Corticospinal Tract Integrity and Long-Term Hand Function Prognosis in Patients With Stroke

Abstract: Background: The restoration of hand function is an important goal for patients with stroke. This study investigated the relationship between corticospinal tract (CST) integrity and the functional status of the hand in patients with stroke 6 months after onset and evaluated which of the following values would be useful for predicting hand function: fiber number (FN), fractional anisotropy (FA) at the mid-pons, and FA at the pontomedullary junction. Methods: The present retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…Many researchers have investigated for uncovering culprit lesion related to upper limb function or establishing the therapeutic methods for recovery of the upper limb. [ 8 , 20 , 23 – 25 ] According to a previous study, the mental practice in chronic stroke patients provided significant reductions in affected arm impairment and significant increases in daily arm function. [ 13 ] The mirror therapy was introduced as 1 component of a home exercise program for chronic stroke patients with task-specific training.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have investigated for uncovering culprit lesion related to upper limb function or establishing the therapeutic methods for recovery of the upper limb. [ 8 , 20 , 23 – 25 ] According to a previous study, the mental practice in chronic stroke patients provided significant reductions in affected arm impairment and significant increases in daily arm function. [ 13 ] The mirror therapy was introduced as 1 component of a home exercise program for chronic stroke patients with task-specific training.…”
Section: Discussionmentioning
confidence: 99%
“…For each fascicle, ROI placement was determined a priori using ROIs either adopted from previous studies or based upon the anatomy of the fascicles as known from other tractography or anatomical studies, as follows. ROIs for AF, IFOF, and UF were placed as in Caverzasi et al (2015); ROIs for FAT were based on Sanvito et al (2020); ROIs for CING were based on the fascicle anatomy as known from Wakana, Jiang, Nagae‐Poetscher, van Zijl, and Mori (2004); seed‐ROI and target‐ROI for CST were placed as in Yoo et al (2019) and Castellano et al (2012), respectively; ROIs for OR were adapted from Chamberland et al (2017) and Chamberland, Tax, and Jones (2018) after lateral geniculate nucleus was identified as shown in Kitajima et al (2015). A more detailed report of anatomical landmarks and references used for ROI placement is displayed in Supplementary Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…ROIs for FAT were based on Sanvito et al (2020); ROIs for CING were based on the fascicle anatomy as known from Wakana, Jiang, Nagae-Poetscher, van Zijl, and Mori (2004); seed-ROI and target-ROI for CST were placed as in Yoo et al (2019) and Castellano et al (2012), respectively; ROIs for OR were adapted from Chamberland et al (2017) and Chamberland, Tax, and Jones (2018) after lateral geniculate nucleus was identified as shown in Kitajima et al (2015). A more detailed report of anatomical landmarks and references used for ROI placement is displayed in Supplementary Table 1.…”
Section: Tractographymentioning
confidence: 99%
“…The relationship between DTI CST images and hand function has been evaluated several times8, 13,14,15,16 ) . Most reports have shown that damage to the CST is useful for predicting the restoration of motor function in patients with stroke13, 16,17,18 ) . Consistent with previous studies, the CST integrity reflected the functional status of the central pontine demyelination in our patients.…”
Section: Discussionmentioning
confidence: 99%